YouTube as Digital Media Platform for Udayana University Students - Richard Togaranta Ginting; Fransiska Timoria Samosir; Majidah; Putu Melati Widya Putri (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Viewers can watch videos produced by media actors on YouTube, a well-known video-sharing platform. It requires searching methods because the volume of content is likewise growing. This study aimed to learn how Udayana University students could retrieve information via YouTube. A quantitative approach through a survey is the research method used. The study's object and population comprised 100 (one hundred) students from 13 (thirteen) distinct departments at Udayana University. Based on the study's results, most students access YouTube for entertainment. Students of Udayana University frequently watch YouTube videos. YouTube information search method does a decent job of choosing videos relevant to video recommendations (79%) but does an inadequate job of using the watch later function (55%).